Improving Long Jump Learning Outcomes Through Middle School Students' Hopscotch Game - Nurhidayat, Budi; Hudain, Muh. Adnan; Kamaruddin, Ilham; Adil, Ahmad; Fahrizal, Fahrizal (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study aims to determine the effectiveness of implementing the hopscotch game in long jump learning for students of public middle school 13 Penajam Paser Utara, as well as to improve students' long jump abilities, including in aspects of landing method, jump angle, support, and starting speed. This study used a classroom action method with two cycles, involving 32 students of class VII C. Measurements were carried out through long jump tests before and after implementing the hopscotch game, with quantitative data analysis to compare student learning outcomes. The results showed a significant increase in students' long jump abilities. The average long jump score in the pre-cycle was 70, increasing to 72.50 in cycle I and reaching 83.44 in cycle II. This increase shows the effectiveness of the hopscotch game in improving students' abilities, with a learning completion percentage reaching 100%. The application of the hopscotch game in long jump learning has proven effective in improving the long jump abilities of students of public middle school 13 Penajam Paser Utara. Therefore, students can utilize the hopscotch game as an engaging alternative learning method to enhance their physical abilities and skills.